The existence value of the Antillean manatee in the unprotected Hondo River (Mexico) as a fundamental component for its conservation - Corona Figueroa, Mildred Fabiola; Ríos Ramírez, José Ney; Castelblanco Martínez, Nataly; Vilchez Mendoza, Sergio José; Delgado Rodríguez, Luis Diego (Journal for Nature Conservation, 2022)
The Hondo River is the natural border between Mexico and Belize, and it is part of the distribution area of the Endangered Antillean manatee Trichechus manatus manatus. Currently, the Hondo River does not have any special protection. Employing qualitative research methods, we documented the social perception and local knowledge from riverside communities to assess conservation status and trends of manatees in the area. Fifty semistructured interviews were carried out to river users in 16 Mexican communities, distributed in six segments along the riverbed. The claims of the inhabitants agree with boat-based surveys: most of the current and historical manatee sightings were reported in segments of the main watercourses, but also in small tributaries, which are usually shallow and rich in aquatic vegetation. Additionally, the local perception about manatee conservation status can be helpful to understand population trends and threats: 48 % of the interviewees claimed that nowadays the number of sighted manatees is less than that observed 10 years ago. The responders identified water pollution due to cane cultivation practices, motorized vessels traffic, and presence of fishing nets as potential threats to manatees. This study provides evidence of relevant local knowledge about the manatee ecology and its habitat, critical in the construction of binational conservation strategies for the species. Therefore, local resources users may play an increasingly significant role in manatee management and monitoring. Although manatees are poached for their meat in several areas of their distribution, the most common value attributed to manatees in Hondo River was non-use existence values. Local people recognize the challenges to observe this cryptic species in this river, but also identified manatees as potential flag species, suggesting that it may represent a valuable resource for ecotourism. We suggest that the non-extractive use of manatees has the potential for promoting species conservation and local economic growth.